1982
DOI: 10.1017/s0003356100000489
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of dairy cattle 8. Relationships of dietary energy intake, changes in live weight, body condition and fertility

Abstract: In each of 2 years, two groups of 25 British Friesian heifers were given, respectively, a moderate-and a low-energy diet for a 12-week period. Mean live-weight gains of 0-25 kg/day and 0-45 kg/day were recorded for the moderate-energy diet, and losses of 0-22 kg/day and 013 kg/day for the low-energy diet. Heifers were inseminated artificially at oestrus at approximately the mid-point of the 12-week period, this oestrus being the next observed after synchronized oestrus, which followed luteolysis induced by clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The percentage conception rate varied between 12 and 33% of animals given the Mo-supplemented diets compared with 58-80% for animals on the other diets. The latter figure was similar to that reported by other authors after the use of prostaglandin synchronization (Leaver, 1977;Baishya et al 1982;Mclntosh, Lewis & Hammond, 1984). The data also suggest that the effect of Mo on conception may be quite rapid, since there was a trend towards a lower conception rate within 8 weeks of a change to a Mo-containing diet in Expt la in cows which were already low in Cu status.…”
Section: Fertilitysupporting
confidence: 91%
“…The percentage conception rate varied between 12 and 33% of animals given the Mo-supplemented diets compared with 58-80% for animals on the other diets. The latter figure was similar to that reported by other authors after the use of prostaglandin synchronization (Leaver, 1977;Baishya et al 1982;Mclntosh, Lewis & Hammond, 1984). The data also suggest that the effect of Mo on conception may be quite rapid, since there was a trend towards a lower conception rate within 8 weeks of a change to a Mo-containing diet in Expt la in cows which were already low in Cu status.…”
Section: Fertilitysupporting
confidence: 91%
“…The relationship between milk yield and fertility of cows has been correlated with body weight, body weight changes and condition score (Baishya et al, 1982;Ducker and Morant, 1984;Ducker et al, 1985;Richards et al, 1986). In order to improve cattle productivity it is useful to start by quantifying the extent to which cattle are affected by nutrition, disease or other environmental factors, especially when large fluctuations in the quantity and quality of forage occur, as they do in seasonally dry tropical and sub-tropical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Leaver (1977) presented results from individually-fed heifers that suggested an interaction between body condition and level of nutrition in relation to pregnancy rate. Baishya, Morant, Pope and Leaver (1982) have found that heifers individually fed to lose weight at insemination (0-2 kg/day) had lower pregnancy rates than heifers gaining weight at that time (0-4 kg/day). These results were not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…
Link to this article: http://journals.cambridge.org/abstract_S0003356100000684How to cite this article: M. J. Ducker, N. Yarrow and S. V. Morant (1982). The effect of change and level of nutrition on the reproductive performance of group-fed dairy heifers.
ABSTRACT

One hundred and sixty Friesian heifers were allocated to two groups 8 or 9 weeks before artificial insemination and group-fed to gain live weight at 0-8 or 0-3 kg/day.

…”
mentioning
confidence: 99%
See 1 more Smart Citation